Electronic structure and properties of NbS2 and TiS2 low dimensional structures - Güller, F. (2012)
Transition metal dichalcogenides have a laminar structure, weakly bound through van der Waals interactions. Due to their technological applications in catalytic processes the bulk structure of many of them has been widely studied in the last 30 years. Some of them, such as NbTe2 and TiSe2, show superconductivity and have been, therefore, the subject of intense study. Novoselov et al. (2005) achieved to isolate not only graphene but also other bidimensional crystals, among them layers of some dichalcogenides. These bidimensional crystals preserve their monocrystallinity under normal ambient conditions, keeping the crystal structure of the bulk. In this contribution we calculate the magnetic and electronic properties of 2D layers of NbS2 (non-magnetic metal in 3D) and TiS2 (non-magnetic semimetal in 3D) as well as quasi 1D chains cut out from these layers.